Dosimetric benefits of 1.5 T MR-guided radiotherapy in partial breast treatment - Jiwon Sung; Gyuri Song; Inho Jeong; Jinsook Ha; Yeona Cho; Joongyo Lee; Jihun Kim (PLoS ONE, 2026)
This study aimed to evaluate the dosimetric benefits of magnetic resonance (MR)-guided radiotherapy (MRgRT) compared to computed tomography (CT)-guided RT for partial breast treatment. First, treatment plan quality was compared between MRgRT with step-and-shoot (S&S) IMRT and CT-guided RT with volumetric-modulated arc therapy (VMAT). Second, the dosimetric benefit of online adaptation in MRgRT was assessed by comparing the initial planned doses with daily MR-defined target geometry to those with planning CT-defined target geometry. Plan quality for MRgRT was comparable to, or slightly lower than, CT-guided RT. The V 95% of the planning target volume (PTV) was lower by 1.72% and 1.94%, respectively, with a lower minimum dose and a higher maximum dose. For the OARs, the dosimetric parameters were generally similar, but for the skin, the D max , D 0.5mL , and D 1mL were slightly higher in MRgRT. Evaluation of the initial planned doses with the daily MR-based target definition resulted in a maximum deviation of 46% for the PTV V 95% , demonstrating uncertainty in CT-based target definition. Although the MRgRT planning quality may be slightly compromised due to the S&S IMRT technique, the dosimetric benefits from online adaptation can be substantial when CT-based target definitions need to be modified based on daily MR imaging guidance.